Increasing the antioxidant capability via the synergistic effect of coupling diphenylamine with sterically hindered phenol. Issue 51 (20th December 2019) - Higgins, Clare L.; Filip, Sorin V.; Afsar, Ashfaq; Hayes, Wayne
Abstract: A series of novel diphenylamine-phenol antioxidants were synthesised that combined the two antioxidant types into a single molecule. These antioxidants were then functionalised with alkyl chains to aid their solubility in hydrocarbon media. As part of a structure-activity study, diphenylamine derivatives were also generated bearing carboxylic acid functionalities in either the ortho, meta or para position with respect to the secondary amine. Methyl or ethyl spacers were also incorporated between the carboxylic acid and the aromatic ring. The antioxidant ability of the diphenylamine-phenols was evaluated using Differential Scanning Calorimetry (DSC) and compared to commercially available antioxidants Irganox L135 and Irganox L57 both as individual components and when blended together. The diphenylamine-phenol antioxidant with an ethyl spacer between the diphenylamine and carboxylic acid in the meta position with respect to the secondary amine functionality showed an impressive oxidation induction time of ca. 24 min in direct comparison with the blend of Irganox L135 and Irganox L57 ( ca . 16 min). Graphical abstract: Image 1 Highlights: Novel diphenylamine-phenol antioxidants Enhancement of the oxidative stability of automotive lubricating oils Intermolecular synergistic effect